Line Managers as Paradox Navigators in HRM Implementation: Balancing Consistency and Individual Responsiveness. (February 2020) - Fu, Na; Flood, Patrick C.; Rousseau, Denise M.; Morris, Tim
Human resource management (HRM) research has broadened its focus beyond the intended HRM designed by executives to include the actual HRM line managers implement. In this study of a global professional services firm, we investigate the content and process of HRM implementation. HRM content refers to the degree or extent to which line managers implement HRM practices. The process of HRM implementation entails two seemingly contradictory dimensions of those practices: consistency (treating team members uniformly) and individual responsiveness (considering individual differences in contributions). Studying 171 employees and their line managers in 60 consulting project teams, we jointly address the effects of consistency and individual responsiveness in line manager HRM implementation. Results indicate that the degree and consistency of HRM implementation by line managers is positively related to individual job performance. In addition, consistency is found to moderate the link between the individual responsiveness of line manager HRM implementation and individual job performance such that the link is stronger when consistency is high. However, no impact is found for team viability. Implications for research and practice are discussed.